Preying on those close to home: witchcraft violence in a Papua New Guinea Village - Jorgensen, Dan (The Australian journal of anthropology, 2014)
Recent attacks on suspected witches in Telefomin led to several deaths and the flight of families in fear of their lives. This violence has much in common with similar events elsewhere in PNG, but there are important differences as well: accusations do not have a misogynist cast (all the targets were men), and the witchcraft is attributed to non-indigenous sources. As in many PNG instances, the police failed to prosecute homicides arising from witchcraft accusations, a fact that has led to widespread local concern. In this paper I present the Telefol cases with a focus on the relation of perpetrators to their victims and to the community at large. I argue that certain aspects of the regional economy combined with a generic witchcraft discourse and the ineffectiveness of the state have fostered a lethal crisis in the relation between villagers and male youth.